2021
DOI: 10.1101/2021.09.29.462374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of intra-modal and cross-modal reward value on visual perception: ERP evidence

Abstract: Stimuli associated with high reward modulate perception and such value-driven effects have been shown to originate from the modulation of the earliest stages of sensory processing in the brain. In natural environments objects comprise multiple features (imagine a rolling soccer ball, with its black and white patches and the swishing sound made during its motion), where each feature may signal different associations with previously encountered rewards. How perception of such an object is affected by the value a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 138 publications
(169 reference statements)
2
13
1
Order By: Relevance
“…However, we note that PR phase in our experiment was only tested after the PC phase, and therefore participants had a long exposure to the reward cues in a setting when they were predictive of the reward delivery when orientation discrimination task was performed correctly (i.e., the PC phase). In contrast, in our previous work (Vakhrushev et al, 2021), we tested the PR phase only after a conditioning phase which employed a different task (i.e., cue localization) than the test phase (i.e., orientation discrimination), and found that reward effects were most prominent for cross-modal cues. Together, the current results and results of our previous study indicate that the effects of reward critically depend on the training mode (Jahfari and Theeuwes, 2017;Failing and Theeuwes, 2018) and the relation between the rewarded stimuli and the task-relevant features.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…However, we note that PR phase in our experiment was only tested after the PC phase, and therefore participants had a long exposure to the reward cues in a setting when they were predictive of the reward delivery when orientation discrimination task was performed correctly (i.e., the PC phase). In contrast, in our previous work (Vakhrushev et al, 2021), we tested the PR phase only after a conditioning phase which employed a different task (i.e., cue localization) than the test phase (i.e., orientation discrimination), and found that reward effects were most prominent for cross-modal cues. Together, the current results and results of our previous study indicate that the effects of reward critically depend on the training mode (Jahfari and Theeuwes, 2017;Failing and Theeuwes, 2018) and the relation between the rewarded stimuli and the task-relevant features.…”
Section: Discussionmentioning
confidence: 72%
“…In total, 43 subjects participated in the experiment to fulfill a target sample size of N = 36 based on a previous study (Vakhrushev et al, 2021). They were invited via an online recruiting system.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations